2000
DOI: 10.1126/science.287.5458.1641
|View full text |Cite
|
Sign up to set email alerts
|

A Potassium Channel Protein Encoded by Chlorella Virus PBCV-1

Abstract: The large chlorella virus PBCV-1, which contains double-stranded DNA (dsDNA), encodes a 94-codon open reading frame (ORF) that contains a motif resembling the signature sequence of the pore domain of potassium channel proteins. Phylogenetic analyses of the encoded protein, Kcv, indicate a previously unidentified type of potassium channel. The messenger RNA encoded by the ORF leads to functional expression of a potassium-selective conductance in Xenopus laevis oocytes. The channel blockers amantadine and barium… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

11
242
0
3

Year Published

2006
2006
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 168 publications
(256 citation statements)
references
References 23 publications
11
242
0
3
Order By: Relevance
“…One peculiarity of the chlorovirus K + channel proteins is that their monomers are small. The most extensively studied channel, K + chlorella virus (Kcv), from the prototype chlorovirus PBCV-1 (named Kcv PBCV-1 ), consists of 94 amino acid residues (Plugge et al, 2000). The monomer of a related chlorovirus, ATCV-1 K + channel (Kcv ATCV-1 ), is only 82 amino acid residues , which is the smallest known K + channel protein.…”
Section: Channel and Transporter Gene Products Coded By Algal Virusesmentioning
confidence: 99%
See 1 more Smart Citation
“…One peculiarity of the chlorovirus K + channel proteins is that their monomers are small. The most extensively studied channel, K + chlorella virus (Kcv), from the prototype chlorovirus PBCV-1 (named Kcv PBCV-1 ), consists of 94 amino acid residues (Plugge et al, 2000). The monomer of a related chlorovirus, ATCV-1 K + channel (Kcv ATCV-1 ), is only 82 amino acid residues , which is the smallest known K + channel protein.…”
Section: Channel and Transporter Gene Products Coded By Algal Virusesmentioning
confidence: 99%
“…One or more representative Kcvs from each of these three groups has been expressed in heterologous cells, including Xenopus laevis oocytes (Plugge et al, 2000) and mammalian cells (Moroni et al, 2002), and shown to produce K + selective currents. They can also complement yeast (Saccharomyces cerevisiae) cells that are defective in K + uptake (Balss et al, 2008;Chatelain et al, 2009).…”
Section: Channel and Transporter Gene Products Coded By Algal Virusesmentioning
confidence: 99%
“…Genes encoding prokaryotic and eukaryotic-like membrane channels are present in some of the phycodnaviruses. We have previously shown that Paramecium bursaria Chlorella virus (PBCV-1), the prototype Chlorella virus (genus Chlorovirus), encodes a gene for a functional potassium ion (K Ï© ) channel, Kcv (3,4). Functional Kcv-like channels exist in 40 other Chlorella viruses infecting the same host (Chlorella NC64A) (5), as well as in another phycodnavirus, Ectocarpus siliculosus virus (6), which infects a marine filamentous brown alga.…”
mentioning
confidence: 99%
“…The most striking feature of the fully functional viral K C channel Kcv is its size of only 94 amino acids Hertel et al 2006;. Besides an appreciable selectivity among cations, the Kcv channel remarkably reveals some voltage sensitivity, although a significant voltage sensor is absent (Plugge et al 2000).…”
Section: (I) Proteins As Natural Nanobiosensorsmentioning
confidence: 99%
“…The viruses of the unicellular green alga genus Chlorella contain double-stranded DNA (Van Etten 2003), and genomic sequencing of these viruses exhibited an open reading frame with all the hallmarks of a K C channel present in all forms of life, i.e. the selectivity filter sequence, two aromatic amino acid residues upstream of the filter, and two transmembrane domains (Plugge et al 2000; figure 4). The most striking feature of the fully functional viral K C channel Kcv is its size of only 94 amino acids Hertel et al 2006;.…”
Section: (I) Proteins As Natural Nanobiosensorsmentioning
confidence: 99%